PENINGKATAN KOMPETENSI GURU MELALUI PELATIHAN ANALISIS SWOT DALAM MENGANALISIS PEMBELAJARAN DI KECAMATAN PACET KABUPATEN BANDUNG - F, Ikka Kartika A; Fitriani, Seni; Lidiawati, Diana; Yuningsih, Yuyun (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This training aims to enhance teachers' competencies in analyzing learning situations using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). Using a descriptive qualitative approach, 25 teachers from various schools in Pacet Subdistrict, Bandung Regency, participated in this program. The training lasted three days and was designed to equip teachers with strategic skills to evaluate teaching conditions comprehensively, including identifying strengths, weaknesses, opportunities, and threats within the local context. The training process included theoretical discussions, group simulations, and individual evaluations, providing hands-on experience for participants. The results showed significant improvements in teachers' reflective and practical abilities to apply SWOT analysis. Teachers developed innovative and adaptive learning strategies based on in-depth analysis of their respective classroom situations. This training also encouraged collaboration among teachers in identifying creative solutions to complex teaching challenges. This article discusses the training stages, the outcomes achieved, and its benefits for teacher professional development. The implications are relevant for planning and implementing educational strategies in the future. This training contributes to improving education quality through a measurable strategic and reflective analysis-based approach. ABSTRAKPelatihan ini bertujuan untuk meningkatkan kompetensi guru dalam menganalisis situasi pembelajaran menggunakan teknik analisis SWOT (Strengths, Weaknesses, Opportunities, Threats). Dengan pendekatan deskriptif kualitatif, 25 guru dari berbagai sekolah di Kecamatan Pacet, Kabupaten Bandung, terlibat dalam program ini. Pelatihan berlangsung tiga hari dan dirancang untuk membekali guru dengan keterampilan strategis dalam mengevaluasi kondisi pembelajaran secara menyeluruh, termasuk mengidentifikasi kekuatan, kelemahan, peluang, dan ancaman dalam konteks lokal. Proses pelatihan mencakup diskusi teoritis, simulasi kelompok, dan evaluasi individu, memberikan pengalaman langsung kepada peserta. Hasil pelatihan menunjukkan peningkatan signifikan dalam kemampuan reflektif dan praktis guru dalam menerapkan analisis SWOT. Guru merancang strategi pembelajaran inovatif dan adaptif berdasarkan analisis mendalam terhadap situasi kelas masing-masing. Pelatihan ini juga mendorong kolaborasi antarguru dalam mengidentifikasi solusi kreatif untuk tantangan pembelajaran yang kompleks. Artikel ini membahas tahapan pelatihan, hasil yang dicapai, dan manfaatnya terhadap pengembangan profesional guru. Implikasi yang dihasilkan relevan untuk perencanaan dan implementasi strategi pendidikan di masa depan. Pelatihan ini memberikan kontribusi terhadap peningkatan kualitas pendidikan melalui pendekatan berbasis analisis strategis dan reflektif yang terukur.